PERBANDINGAN PENGENAAN PAJAK E-COMMERCE B2C ANTARA INDONESIA DENGAN SINGAPURA - Hafizh Aryo Dhaneswara; RR. Adeline Melanie (Gloria Justitia, 2021)
The development of information and communication technology nowadays has an impact on the trade sector. According to data from Badan Pusat Statistika and Kominfo, trade carried out through electronic media makes economic growth expeditious. Trading through electronic media is commonly referred to as E-commerce. Online stores are one of the fastest growing types of e-commerce businesses in Indonesia, an example of e-commerce in Online Stores is Business to Consumer (B2C). Indonesia as one of the e-commerce user countries with the largest number of transactions in Southeast Asia, however, e-commerce taxation regulations in Indonesia are still enforced the same as ordinary conventional stores, causing problems in taxation, especially in the imposition of B2C e-commerce taxes. Tax authorities find it difficult to determine the imposition of the amount of tax owed to e-commerce taxpayers. The writing method used by this author is a normative juridical method, where the method is carried out by looking for instructions in documents or library materials, or better known as document studies. Indonesia already has regulations for imposing taxes on e-commerce transactions, but there are no regulations for imposing taxes on certain types of e-commerce. In the implementation of the imposition of B2C e-commerce taxes in Indonesia, there are still many obstacles that are limited by inadequate regulations and systems. Reflecting on the state of Singapore, Indonesia must have special regulations and adequate systems for B2C e-commerce so that existing obstacles can be resolved properly.